The Diversity of Mammalian Hemoproteins and Microbial Heme Scavengers Is Shaped by an Arms Race for Iron Piracy - Mozzi, Alessandra; Forni, Diego; Clerici, Mario; Cagliani, Rachele; Sironi, Manuela (Frontiers in Immunology, 2018)
Abstract Iron is an essential micronutrient for most living species. In mammals, hemoglobin (Hb) stores more than two thirds of the body's iron content. In the bloodstream, haptoglobin (Hp) and hemopexin (Hpx) sequester free Hb or heme. Pathogenic microorganisms usually acquire iron from their hosts and have evolved complex systems of iron piracy to circumvent nutritional immunity. Herein, we performed an evolutionary analysis of genes coding for mammalian heme-binding proteins and heme-scavengers in pathogen species. The underlying hypothesis is that these molecules are engaged in a molecular arms race. We show that positive selection drove the evolution of mammalian Hb and Hpx. Positively selected sites in Hb are located at the interaction surface with Neisseria meningitidis heme scavenger HpuA and with Staphylococcus aureus iron-regulated surface determinant B (IsdB). In turn, positively selected sites in HpuA and IsdB are located in the flexible protein regions that contact Hb. A residue in Hb (S45H) was also selected on the Caprinae branch. This site stabilizes the interaction with Trypanosoma brucei hemoglobin-haptoglobin (HbHp) receptor (TbHpHbR), a molecule that also mediates trypanosome lytic factor (TLF) entry. In TbHpHbR, positive selection drove the evolution of a variant (L210S) which allows evasion from TLF but reduces affinity for HbHp. Finally, selected sites in Hpx are located at the interaction surface with the Haemophilus influenzae hemophore HxuA, which in turn displays fast evolving sites at the Hpx-binding interface. These results shed light into host-pathogens conflicts and establish the importance of nutritional immunity as an evolutionary force.